Bio-inspired special wettability in oral antibacterial applications - Zhang, Xin; Bai, Rushui; Sun, Qiannan; Zhuang, Zimeng; Zhang, Yunfan; Chen, Si; Han, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Most oral diseases originate from biofilms whose formation is originated from the adhesion of salivary proteins and pioneer bacteria. Therefore, antimicrobial materials are mainly based on bactericidal methods, most of which have drug resistance and toxicity. Natural antifouling surfaces inspire new antibacterial strategies. The super wettable surfaces of lotus leaves and fish scales prompt design of biomimetic oral materials covered or mixed with super wettable materials to prevent adhesion. Bioinspired slippery surfaces come from pitcher plants, whose porous surfaces are infiltrated with lubricating liquid to form superhydrophobic surfaces to reduce the contact with liquids. It is believed that these new methods could provide promising directions for oral antimicrobial practice, improving antimicrobial efficacy.